The Influence of Corporate Social Responsibility Disclosure, Acceptance of Going Concern Audit Opinion and Audit Quality on Abnormal Returns - YUDHA, Fairas Panca (PT Keberlanjutan Strategis Indonesia, 2024)
This research aims to examine the influence of CSR disclosure, acceptance of going concern audit opinion and audit quality on market reactions as measured by abnormal returns. The information content in Corporate Social Responsibility (CSR) disclosure, receipt of going concern audit opinion and audit quality are signals from the company that are predicted to cause a market reaction. The sample was obtained using a purposive sampling method and 20 mining sector companies listed on the Indonesia Stock Exchange in 2010-2013 were selected. The analytical method used in this research is multiple regression analysis. The results of hypothesis testing show that CSR disclosure, acceptance of going concern audit opinion, audit quality, company size and asset growth rate simultaneously influence abnormal returns. Meanwhile, partial CSR disclosure, acceptance of going concern audit opinion and audit quality do not affect abnormal returns. This implies that financial information is still a reference for investors in making investment decisions. They do not pay much attention to CSR disclosure information, going concern audit opinion and audit quality as a tool for predicting the future. This also shows that the characteristics of investors in the Indonesian capital market are more long-term oriented.